Preparation, characterization and reduction of burst release of insulin from biodegradable PLGA microspheres - Rahman, Md. Mokhlesur; Rezaul Haque, Ansary; Mohamed, Awang; Katas, Haliza (2015)
In conventional method, insulin is injected subcutaneously two to four times a day before each meal to maintain the serum glucose level of diabetic patients [1]. This multiple injection routine is complex, painful, inconvenient and fear of hypoglycemia. To improve patient compliance and convenience, poly(lactide-co-glycolide) (PLGA) based sustained release formulation of insulin delivery has been developed [2]. Generally, the major drawbacks in the development of insulin loaded PLGA microspheres are the high initial burst and incomplete release of encapsulated insulin [3]. Initial burst release means the release of insulin within 24 hours of release studies. Moreover, PLGA microspheres tend to have a very slow or near to zero release of insulin after the initial burst. The slow or no release period is often referred to as the “lag phase” and continues until extensive degradation of PLGA starts. During this period, the patient may not be effectively treated due to the lack of sufficient insulin release [4]. In this study, insulin encapsulated PLGA microspheres have been prepared using a fast degrading hydroxyl terminated–PLGA (PLGA-OH) to reduce the initial burst release and to remove the lag phase with a view to achieve controlled release of insulin.